2018
DOI: 10.1002/joa3.12141
|View full text |Cite
|
Sign up to set email alerts
|

SMART pass will prevent inappropriate operation of S‐ICD

Abstract: BackgroundCompared to screening ECG before implantation of a subcutaneous implantable cardioverter‐defibrillator (S‐ICD), selectable vectors without T‐wave oversensing increase after S‐ICD implantation. Newer algorithms have recently become available to reduce T‐wave oversensing, such as SMART pass (SP). With this function, more selectable vectors are identified after S‐ICD implantation. However, this improvement in eligibility utilizing SP has not yet been well validated. We aimed to clarify S‐ICD eligibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“… 6 The majority of inappropriate shocks were resulting of T-wave oversensing. A significant overall reduction in inappropriate therapy was seen in dual-zone programming 2 , 22 as well as the new SMART-PASS 23 algorithm of advanced technology with second-generation S-ICD. All our S-ICD patients were implanted with a second-generation Emblem S-ICD with new SMART-PASS algorithm and had dual-zone programming, resulting in complete absence of inappropriate therapies due to T-wave oversensing.…”
Section: Discussionmentioning
confidence: 99%
“… 6 The majority of inappropriate shocks were resulting of T-wave oversensing. A significant overall reduction in inappropriate therapy was seen in dual-zone programming 2 , 22 as well as the new SMART-PASS 23 algorithm of advanced technology with second-generation S-ICD. All our S-ICD patients were implanted with a second-generation Emblem S-ICD with new SMART-PASS algorithm and had dual-zone programming, resulting in complete absence of inappropriate therapies due to T-wave oversensing.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have demonstrated that MRI could be performed with no significant clinical effects and no differences in the type and number of complications in patients who had a pacemaker that was non-MRI-compatible compared with patients with MRI-compatible devices, taking the necessary precautions and applying a safety protocol. (3,4) This protocol consists in programming the pacemaker to an asynchronous pacing mode in pacingdependent patients, or inhibiting it (turning it off) in non-pacing-dependent cases, and in the inhibition of tachycardia monitoring and deactivation of therapies in patients with defibrillators. ( 4)…”
Section: Percentage Of Patients With Cardiac Electronic Devices Requiring Magnetic Resonance Imagingmentioning
confidence: 99%
“…(5) However, two recently published studies that included more than 2,500 patients who received MRI with 1.5 T scanner showed no significant complications applying the safety protocol. (3,4) It should be pointed out that devices implanted before certain dates (pacemakers prior to 1998 or defibrillators prior to 2000) were taken as contraindication in these studies.…”
Section: Percentage Of Patients With Cardiac Electronic Devices Requiring Magnetic Resonance Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Пациенту 18 лет c гипертрофической кардиомиопатией (ГКМП) и осложненным семейным анамнезом (ВСС отца с ГКМП) с классом показаний для имплантации ИКД IIa согласно национальным рекомендациям по определению риска и профилактике ВСС [6] [4]. Однако, в этой публикации была показана большая частота неадекватных шоков в течение…”
unclassified